The Effectiveness of the Quiz Team Learning Model on Islamic Education Learning Outcomes of Eighth-Grade Students at SMP Negeri 2 Tinambung - Randi Sudirman; Marjanah Marjanah (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
This study evaluates the effectiveness of the Quiz Team active-learning model in improving Islamic Education (PAI) learning outcomes among eighth-grade students at SMP Negeri 2 Tinambung. A one-group pretest–posttest pre-experimental design was employed, involving 29 students who received Quiz Team instruction across five meetings. Data were collected using validated multiple-choice pretests and posttests, supported by standardized classroom implementation observations. Data were analyzed using SPSS through descriptive statistics, Kolmogorov–Smirnov normality testing, Levene’s homogeneity testing, paired-sample t-testing at α = 0.05, and effect size reporting. The findings show that implementation fidelity improved across sessions, from 82.95% to 89.77% and then to 92.04%, indicating rapid adaptation by both teachers and students. Students’ initial mastery was low, as reflected in the pretest score (M = 35.07, SD = 8.14), whereas the posttest score showed substantial improvement (M = 78.79, SD = 6.89), with a mean increase of 43.65 points. The statistical assumptions were met, with normality values of p = 0.816 for the pretest and p = 0.863 for the posttest, and homogeneity value of p = 0.383. The paired-sample t-test confirmed a highly significant improvement in learning outcomes (t = 28.152, p < 0.001). These findings indicate that the Quiz Team model can enhance student engagement and conceptual mastery in PAI through retrieval practice, peer explanation, and rapid formative feedback. This study contributes to the literature on active learning in Islamic education by providing empirical evidence on the effectiveness of Quiz Team instruction. However, the single-group design and single-site sample limit causal inference and generalizability. Further research is recommended through controlled trials, larger and more diverse samples, longer follow-up periods to assess retention, and process evaluations to identify active components for scalable implementation.